Anthropometric Profile of Diabetes Mellitus Type 2, Hypertension and Dyslipidaemia in an Outpatient Clinic of a Tertiary Care Hospital in Dehradun - Sharma, Richa; Ankit Paliwal, Rajesh Sharma, (International Journal of Innovative Research in Medical Science, 2017)
The approximate prevalence of the metabolic syndrome in patients with coronary heart disease (CHD) is 50%, with a prevalence of 37% in patients with premature coronary artery disease (age 45), particularly in women. With appropriate cardiac rehabilitation and changes in lifestyle (e.g., nutrition, physical activity, weight reduction, and, in some cases, Drugs), the prevalence of the syndrome can be reduced.[1] It is vital to understand that this measures of humans i.e. anthropometry is infact a function of total fat and its distribution in the body. This logically applies the fact that these measures would be more useful in disorders associated with abnormal fat metabolism and disorders related to its distribution. In the recent times a clustering of such metabolic abnormalities named as metabolic syndrome has emerged as an epidemic. It was described by Revan who described it as syndrome X (1988) and proposed that insulin resistance is a common denominator. He also suggested it as a cluster of metabolic abnormalities including hypoalpha - lipoprotinemia, hypertriglyceridemia, hyperinsulinemia and increased blood pressure.[2] It has been realized that these body measurement indices vary according to the region, race, geneticmakeup and even with age. Hence the applicability of the above mentioned factors could not be decided and different criteria based on the population based studies were considered. With the development of imaging techniques to measure centralfat precisely and to distinguish particularly intra-abdominal (visceral) from subcutaneous fat, several studies have shownthat central fat accumulation is predictive of the featuresof the metabolic syndrome.[3] In clinical and epidemiological studies, obesity is stronglyassociated with all cardiovascular risk factors. However, themechanisms underlying the association between central obesity (particularly visceral obesity) and the metabolic syndrome arenot fully understood and are likely to be complex.